The Impact of the Investment Climate on Employment Growth : Does Sub-Saharan Africa Mirror Other Low-Income Regions? - Aterido, Reyes; Hallward-Driemeier, Mary (2012)
Using survey data from 86,000 enterprises in 104 countries, including 17,000 enterprises in 31 Sub-Saharan African countries, this paper finds that average enterprise-level employment growth rates are remarkably similar across regions. This is true despite significant differences in the quality of the investment climate in which these enterprises operate. Objective measures of investment climate conditions (including the number of outages, the share of firms with bank loans, and others) indicate that conditions are most challenging within Sub-Saharan Africa, as well as for smaller enterprises. However, enterprises employment in Sub-Saharan Africa is less sensitive to changes in access to infrastructure and finance relative to other low-income regions. This can be understood by looking at non-linear effects by firm size -- and the finding that these size effects are particularly strong within Sub-Saharan Africa. Although unreliable infrastructure services and inadequate access to finance generally hamper growth, in Sub-Saharan Africa they are actually associated with higher employment growth rates among micro enterprises. Although employment growth is good news in Sub-Saharan Africa, that much of the expanded employment is in small, labor-intensive, less productive enterprises raises longer-run concerns about the efficiency of the allocation of resources and aggregate productivity growth in the region.